2023
DOI: 10.5455/jabet.2023.d144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine-loaded silver nanoparticles on minerals concentration and antibacterial activity in rats

Abstract: Background: Caffeine boosts metabolism and the neurological system. When extreme weakness or sleepiness occurs, it is used recreationally and medicinally to reduce physical and mental fatigue. Caffeine initially stimulates the central nervous system, increasing intellect, speed, accuracy, focus, and coordination. Objective: To evaluate how caffeine nanoparticles affect potassium, calcium, zinc, and magnesium levels, in addition, the anti-bacterial activity of the samples has been employed. Methods: Eighteen ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Overall, higher propolis extract concentrations had larger inhibition zones, while antibiotics, especially gentamicin, were consistently effective. The antibacterial activity observed in our findings surpasses that reported in the study conducted by Rasheed et al (2023), regarding the antibacterial effects of propolis against S. aureus and E. coli. A study by Sanchez-Moreno et al (1998) found that a concentration of 5.48 mg/ml had moderate zone inhibition ranging from 13.0 ± 0.09 to 15.0 ± 0.11 mm against these two bacteria.…”
Section: Antibacterial Activitycontrasting
confidence: 80%
“…Overall, higher propolis extract concentrations had larger inhibition zones, while antibiotics, especially gentamicin, were consistently effective. The antibacterial activity observed in our findings surpasses that reported in the study conducted by Rasheed et al (2023), regarding the antibacterial effects of propolis against S. aureus and E. coli. A study by Sanchez-Moreno et al (1998) found that a concentration of 5.48 mg/ml had moderate zone inhibition ranging from 13.0 ± 0.09 to 15.0 ± 0.11 mm against these two bacteria.…”
Section: Antibacterial Activitycontrasting
confidence: 80%
“…The enzymatic reaction is represented by equation ( 9): 2GHS + NAPD l ↔ GSSG + NAPDH + H l (9) Inhibition of glutathione reductase results in a decrease in the level of reduced glutathione (GSH) and an increase in the level of glutathione disulfide (GSSG). Nicotinamide adenine dinucleotide phosphate (NADPH) is crucial for regenerating glutathione, and this process is essential for resisting oxidative stress and maintaining intracellular pH Rasheed et al, 2023). Therefore, studying the inhibition of glutathione reductase is a valuable approach for identifying potential antioxidants.…”
Section: Homogeneous Kineticsmentioning
confidence: 99%
“…In silico ADME study was carried out to predict the adverse metabolic effects of oral administration of TPPH o-methyl and TbPPH as drug candidate, as well as their half-life in the organism and excretion route (Silvino et al, 2016). Cytochrome P450 isoenzymes (CYP450) are oxidases that interact with drugs in order to decrease their plasma concentration and reduce the risks of toxicity by metabolic activation Rasheed et al, 2023), as well as making them more water soluble for elimination (Eitrich et al, 2007;LANEZ et al, 2023). Thus, a drug candidate should not inhibit cytochrome CYP450 isoenzymes because inhibition may increase the plasma concentration (Zahno et al, 2011;Terkeltaub et al, 2011).…”
Section: Adme Studymentioning
confidence: 99%